El proconsulado de la Bética en el cursus honorum senatorial - Navarro, Francisco Javier (Gerión. Revista de Historia Antigua, 2005)
This paper aims to demonstrate that the status of the province of Baetica within the Roman Empire was much greater than has previously been believed. For a long time it has been thought that the sphere of jurisdiction of the senate was for those members of the ordo who lacked either the emperor’s backing or the solid support of their allies, so that if a senator of praetorian rank was designated to govern a proconsular province, this was considered an obstacle to his career. None the less, it can be shown that government of Baetica did not represent a hiatus in a senator’s cursus, and this province was not undervalued, as might have been the case with others whose government was not attractive to senators desiring promotion.